Correction to: FAM83B inhibits ovarian cancer cisplatin resistance through inhibiting Wnt pathway - He, Shanyang; Wang, Wei; Wan, Zhiyong; Shen, Hongwei; Zhao, Yunhe; You, Zeshan; Liu, Jun; Zhu, Liwen (Oncogenesis (New York, NY), 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41389-021-00303-4